Genetic diversity and salt tolerance assessment of 51 alfalfa (Medicago sativa) varieties under saline soil conditions - Fan, Shugao; Chen, Jianmin; Mu, Jinpeng; Zhang, Mingjun (Frontiers in Sustainable Food Systems, 2023)
Introduction Salt stress significantly impacts plant growth worldwide. Although alfalfa exhibits some tolerance to salt-alkali soils, the specific salt tolerance levels across different alfalfa varieties remain inadequately understood. For this purpose, we conducted a study to investigate the diversity of agronomic traits of alfalfa (Medicago sativa) under different soil environments in order to elucidate the salt tolerance of 51 alfalfa varieties. Methods We chose three different soil conditions for our study: normal conditions in Yantai as control, saline conditions in Yantai with soil salt concentrations ranging from 0.25 to 0.33%, and saline-alkali conditions in Dongying with soil salt concentrations ranging from 0.28 to 0.32%. We chose 51 alfalfa varieties from different sources as our experimental materials. Planting was conducted following a completely randomized block design with three replicates for each variety. Harvesting was performed when the plants reached 50% flowering, cutting them at a height of 5 cm above the ground. Comprehensive assessments encompassed 10 parameters, namely fresh weight, dry weight, stem-leaf ratio, branch count, plant height, crude protein content, crude fat content, acid detergent fiber, neutral detergent fiber, and ash content. Results Our findings revealed that the 51 studied alfalfa varieties displayed significant generalized heritability and coefficient of variation, indicating a high level of genetic diversity. Using principal component and cluster analyses, we categorized the varieties into three distinct clusters based on their agronomic traits. Grey correlation degree analysis revealed the commendable performance of Ying st, PI 672734, and Mei zuo across diverse environments. Genotype emerged as a predominant determinant of all parameters, except crude fat, acid detergent fiber, and neutral detergent fiber. Through the application of membership function analysis, PI 672768 emerged as a variety that demonstrated strong tolerance in both saline soil contexts. Discussion Despite extensive previous studies indicating Zhong Mu No. 1 as a salt-tolerant alfalfa variety, its performance in this experiment did not distinguish itself. The findings of this study provide a fundamental basis for improving the management of saline-alkali lands and advancing alfalfa cultivation practices.